2020
DOI: 10.1136/bmjopen-2019-036077
|View full text |Cite
|
Sign up to set email alerts
|

Implementing post-discharge care following acute kidney injury in England: a single-centre qualitative evaluation

Abstract: ObjectivesWe sought to understand the factors influencing the implementation of a primary care intervention to improve post-discharge care following acute kidney injury (AKI).DesignQualitative study using semi-structured interviews and thematic analysis.SettingGeneral practices in one Clinical Commissioning Group area in England.ParticipantsA total of 18 healthcare staff took part in interviews. Participants were practice pharmacists, general practitioners, practice managers and administrators involved in impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The analysis of our qualitative data showed that the events were generally well received. 34 Participants reported that after attending, they felt better equipped to implement the intervention. GPs and practice managers welcomed the opportunity to find out how their peers in local practices were approaching implementation, while pharmacists particularly appreciated the clinical content which helped increase their knowledge about kidney health.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis of our qualitative data showed that the events were generally well received. 34 Participants reported that after attending, they felt better equipped to implement the intervention. GPs and practice managers welcomed the opportunity to find out how their peers in local practices were approaching implementation, while pharmacists particularly appreciated the clinical content which helped increase their knowledge about kidney health.…”
Section: Resultsmentioning
confidence: 99%
“…However, others felt constraints of their roles limited potential involvement in care for patients following AKI. 34 …”
Section: Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Of equal importance to the clinical information that a discharge document holds is its use for coding and reimbursement purposes. Failure to record an episode of AKI treated with KRT can have serious implications and affect patients' future or long-term management ( 34 ).…”
Section: Discussionmentioning
confidence: 99%